2015
DOI: 10.1182/blood.v126.23.1362.1362
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Acute Myeloid Leukemia with a New CXCR4 Antagonist IgG1 Antibody (PF-06747143)in NOD/SCID Mice

Abstract: Chemoresistance represents a considerable barrier to improving outcomes for patients with acute myeloid leukemia (AML) and therapeutic approaches using multiple lines of therapy have been unsuccessful as cancer cells acquire resistance to the chemotherapeutic agents to which they are exposed. This vulnerable patient group needs individualizing therapy through careful selection of appropriate agents based on specific signaling pathways. The chemokine receptor CXCR4 mediates cell anchorage in the bone marrow mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been shown, in preclinical studies, not only to inhibit CXCR4 activation and migration but also to induce apoptosis of CLL cells at nanomolar concentrations, in the presence or absence of stroma support [36]. It has been used in association, in clinical trials for the treatment of relapsed/refractory multiple myeloma and acute myeloid leukemia patients, with encouraging results [37,38].…”
Section: Cxcr4 Mutation and Targeted Therapymentioning
confidence: 99%
“…It has been shown, in preclinical studies, not only to inhibit CXCR4 activation and migration but also to induce apoptosis of CLL cells at nanomolar concentrations, in the presence or absence of stroma support [36]. It has been used in association, in clinical trials for the treatment of relapsed/refractory multiple myeloma and acute myeloid leukemia patients, with encouraging results [37,38].…”
Section: Cxcr4 Mutation and Targeted Therapymentioning
confidence: 99%
“…52 PF-06747143 exerts its anti-leukemic impact similarly as monotherapy in primary models of AML xenograft. 53 These pre-clinical data, alongside with assumed mechanisms for AML, propose that anti-CXCR4 MAb may have promising effects in clinical applications; however, their toxic adverse effects on the processes of normal hematopoiesis deserved to be well elucidated in future studies.…”
Section: Ly2624587mentioning
confidence: 99%
“…Preclinical data for the anti-CXCR4 IgG1 monoclonal antibody, PF-06747143, were recently presented at the Annual Meeting of the American Society of Hematology; the authors suggested that CDC and ADCC are mechanisms involved in the antileukemia effect in AML cell lines [ 29 ]. PF-06747143 exerted an antileukemia effect as monotherapy in primary AML xenograft models [ 30 ]. Overall, the preclinical data, as well as the plausible additional mechanisms for AML, suggest that anti-CXCR4 monoclonal antibodies have promise in clinical applications, while also raising concerns about toxicity in the process of normal hematopoiesis.…”
Section: Cxcr4 Inhibitors: Preclinical Datamentioning
confidence: 99%